Independent Predictors of Recurrence of Vertigo Among Nigerians - Sogebi OA; Oyewole AE (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: Recurrence of vertigo indicates a morbidity to the patient and a dilemma for the managing physician. Objectives: To describe the characteristics of vertigo, document prevalence and explore the characteristics which could independently predict recurrence of vertigo. Methods: A cross-sectional study of patients managed for vertigo in a tertiary facility was retrospectively done. Patients' demographic and clinical characteristics, associations of vertigo, audiological symptoms, comorbid illnesses, and duration to achieve control of vertigo were recorded. Recurrence of vertigo was used to categorize the patients. The factors that were associated with recurrence on univariate analyses were evaluated as independent predictors of recurrence of vertigo. Results: The 73 patients with a male-to-female ratio of 1:1.4 were aged 35 -78 (mean 56.6±9.9) years. The associated symptoms included body weakness (34.2%), audiological symptoms (38.4%), 27.4% had antecedent head and neck injury and vertigo was precipitated or aggravated by changes in the head and neck position in 63.0% Vertigo was controlled within 1 -7 (Median 2) days, 35.6% had a recurrence of vertigo. Age, the experience of nausea and vomiting, previous head and neck injury, presence of comorbidity, and long duration to achieve control of vertigo were significantly associated with recurrence of vertigo. All these factors except the presence of comorbidity could independently predict the recurrence of vertigo. Conclusion: Vertigo is common in adult females, and mostly positional in type. About a third of patients may have a recurrence of vertigo. Age, especially above 57 years, nausea and vomiting, head and neck injury and prolonged period to control vertigo may independently predict recurrence of vertigo.